Pandangan Lansia tentang Seksualitas pada Lanjut Usia - Pambudi, Hubertus Agung; Dwidiyanti, Meidiana; Wijayanti, Diyan Yuli (Jurnal Kesehatan, 2018)
The physiological, cognitive and psychosocial changes which occur in the elderly can have an impact on the elderly’s decreased ability to meet functional needs, confusion or withdrawal, and an inability to make needs-related decisions. The physical changes include some changes in the appearance, different alterations in internal organ systems, changes in psychological function and nervous system, as well as changes in the sexuality appearance and ability. The purpose of this study was to investigate sexuality experiences of the elderly in the society. This study used a qualitative design with a hermeneutic phenomenological approach. The samples were three elderly people recruited using purposive sampling technique. The steps in analyzing the data included data collection analysis, data reduction, verification, and conclusion. The findings revealed that sexual intercourse in the elderly served a part of worship and efforts made to maintain the family harmony. Based on findings, it is recommended that the health service units work together with the health volunteers of the elderly health service post to provide correct information through health education about sexuality so that the elderly can gain an understanding of sexuality to improve their quality of life.